Analysis in Factors of Influencing the Community Health Center Employee Performance: Literature Review - Moriskha, Moriskha; misnaniari, Misnaniarti; Flora, Rostika; Fajar, Nur Alam; Windusari, Yuanita (Indonesian Journal of Global Health Research, 2024)
One of the aspects which describes the services’ quality at the Health Center is reflected by the result of human resources’ performance as the service implementer. Many factors influence the employee’ performance at the Health Center in which among them are workload, motivation, leadership and Occupational Safety and Health (K3) The purpose of this study is to analyze factors that influence employee performance in community health centers. This article aims to review the available literature about the influence of the workload, motivation, leadership, and Occupational Safety and Health (K3) on the health centers employee’ performance. The methods used are Systematic Literature Review using channel Preferred Reporting Items for Systematic Literature Review (PRISMA) by collecting articles from Google Scholar and PubMed databases with the keywords workload, motivation, leadership, and Occupational Safety and Health (K3). From the analysis results, 17 relevant articles are selected with the relevant criteria. The conclusion is that workload, motivation, leadership, and Occupational Safety and Health (K3) have a significant influence on health centers employee’ performance.